2016
DOI: 10.5294/pacla.2016.19.4.6
|View full text |Cite
|
Sign up to set email alerts
|

The Contextualization of the Watchdog and Civic Journalistic Roles: Reevaluating Journalistic Role Performance in U.S. Newspapers

Abstract: This study examines the two dominant U.S. journalism models-the watchdog and civic-oriented professional performance-in the aftermath of the economic crises. The study, based on a content analysis of 1,421 news stories published by five national U.S. dailies, measures journalists' role conception through a content analysis of newspaper articles, examining the concept of journalistic role performance. The findings indicate different contextualizations of the two roles: The civic journalism performance was mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
0
6
0
4
Order By: Relevance
“…This study makes use of a set of indicators that measure journalistic roles in news proposed by Mellado (2015) which have been validated in different cultural settings (Hellmueller et al 2016; Mellado et al 2017; Mellado and van Dalen 2017; Wang et al 2017). This framework includes the operationalization of six professional roles in news: the interventionist, the watchdog, the loyal-facilitator, the infotainment, the service and the civic roles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study makes use of a set of indicators that measure journalistic roles in news proposed by Mellado (2015) which have been validated in different cultural settings (Hellmueller et al 2016; Mellado et al 2017; Mellado and van Dalen 2017; Wang et al 2017). This framework includes the operationalization of six professional roles in news: the interventionist, the watchdog, the loyal-facilitator, the infotainment, the service and the civic roles.…”
Section: Methodsmentioning
confidence: 99%
“…Our study analyzes the performance of journalistic roles between television news and the print press, drawing on a set of empirical indicators and a conceptual framework developed around the concept of journalistic role performance, which has gained importance within the field of journalism studies (Hellmueller et al 2016; Mellado 2015; Mellado, Hellmueller and Donsbach 2017; Mellado et al 2017; Mellado and van Dalen 2017; Tandoc et al 2013; Wang et al 2017, among others). This stream of research grew in part out of the insight that survey-based research might not reflect actual manifestation of professional roles in practice (Mellado and van Dalen 2014; Patterson and Donsbach 1996; van Dalen et al 2017; D.…”
Section: Journalistic Role Performance In Newsmentioning
confidence: 99%
“…Other scholars have described watchdog journalists as ‘propagandist’ (Pasti, 2005), ‘lapdogs’ (Donsbach, 1995), or ‘guard dogs’ (Donohue et al, 1995). In a content analysis of US newspaper articles, Hellmueller et al (2016) found an even higher tendency to perform the civic-oriented model than the watchdog model in newspaper coverage. Mellado (2015) distinguished the watchdog role from a civic-oriented role as two different dimensions belonging to power relations and audience-approach domains.…”
Section: Professional Journalism and Political Lifementioning
confidence: 99%
“…Esta línea teórica en los abordajes del periodismo ha adquirido mucha importancia en la última década (Hellmueller, Mellado, Bluebell & Huemmer, 2016;Mellado, Hellmueller & Donsbach, 2017;Mellado & Van Dalen, 2017;Tandoc, Hellmueller & Vos, 2013;Wang, Sparks, Lu & Huang, 2017), en gran medida por la incapacidad de los estudios normativos para explicar la práctica profesional, pero también por su sofisticación metodológica. En efecto, esta corriente de investigación tomó notoriedad por resultados que evidenciaron que los trabajos que empleaban encuestas a los periodistas, no reflejaban necesariamente la detección de los roles profesionales en la práctica (Mellado & Van Dalen, 2014;Patterson & Donsbach, 1996;Van Dalen, 2012;Weaver & Wilhoit, 1996).…”
Section: Práctica Periodísticaunclassified